Is fixation of a single end of flail segment rib fractures enough? - Nicholas Pelz; Anthony Perugini; James Iandoli; Daniel DeGenova; Anthony Melaragno; Mallory Faherty; Benjamin C Taylor (Trauma Surgery & Acute Care Open)
Background Segmental rib fractures in blunt thoracic trauma present with increased morbidity and mortality with an association of increased pulmonary insult and concomitant injuries. There is a paucity within the literature regarding the necessity of fixation of one or both segments of rib fractures in a flail chest. This study aimed to analyze surgical rib fixation and assess outcomes for non-fixed fractured rib ends in segmental rib fractures.Methods This is a retrospective review of 125 patients who underwent open reduction internal fixation of flail segmental rib fractures at our urban Level 1 trauma center. Initial plain films and CT were compared with follow-up plain film imaging at 3 months to assess radiographic outcomes, fracture healing, fixation failure, or residual deformity. Clinical outcomes such as length of intensive care unit (ICU) stay, length of ventilatory support, associated pneumonia, duration until chest tube removal, and need for additional rib surgery were analyzed.Results Fixation of a single end of segmental rib fractures and flail segments was associated with decreased incidence of fracture union at 3 months postoperatively (43/55 vs 65/70, respectively; p=0.018) but failed to show any difference in fracture collapse (50/55 vs 67/70, respectively; p=0.223). There were no differences between postoperative ICU length of stay (4.18±5.54 vs 4.62±4.48 days, respectively; p=0.690), postoperative ventilatory status (29/55 vs 38/70, respectively; p=0.840), duration of ventilatory support (3.52±4.69 vs 4.34±5.87, respectively; p=0.430), or associated pneumonia (7/55 vs 8/70, respectively; p=0.770).Conclusions These data support that fixation of both sides of flail segment rib fractures results in improved rib fracture union at 3 months postoperatively. However, fixation of both sides of flail segments does not appear to result in any difference in fracture collapse or clinical perioperative outcomes.Level of Evidence Therapeutic Level III